Long-Term Survival Effects of Preoperative Breast MRI in Patients with Breast-Conserving Surgery - Ahmet Serkan Ilgun; Dauren Sarsenov; Gul Alco; Alper Ozturk; Filiz Agacayak; Filiz Elbuken; Zeynep Erdogan; Kezban Nur Pilanci; Cetin Ordu; Fatma Aktepe; Gursel Soybir; Vahit Ozmen (Acta Clinica Croatica, 2022)
The benefit of breast magnetic resonance imaging (MRI) in breast-conserving surgery (BCS) is unclear. Our study compared breast cancer patients with and without preoperative breast MRI and their long-term oncologic outcomes are reported. A total of 1378 BCS cases with early breast cancer between 1996 and 2017 were reviewed. Patients with carcinoma in situ or neoadjuvant treatment or having breast MRI after tumor excision were excluded. Of 1378 patients, 270 (19.5%) had preoperative MRI. There were no significant differences regarding T and N stage and molecular subtypes between the groups. Surgical margins were significantly wider in the breast MRI group. Five-year overall survival (OS) was 96.9% in the MRI group and 94.3% in the control group, and this difference was not significant (p=0.11). Five-year local-regional recurrence-free survival (LRFS) was not significantly different either (98.8% and 96.5%, respectively, p=0.41). When analyses were repeated only for patients with hormone receptor-negative or triple-negative breast cancer, there was still no significant difference in OS, LRFS, or disease-free survival. In conclusion, MRI does not seem necessary in all patients undergoing BCS. New prospective randomized controlled trials are needed to determine appropriate use of preoperative MRI and its effects on oncologic outcomes in early breast cancer patients.